Herpesvirus infections in adenoids in patients with chronic adenotonsillar disease - Ivaska Lotta E; Silvoniemi Antti; Mikola Emilia; Puhakka Tuomo; Waris Matti; Vuorinen Tytti; Jartti Tuomas (WILEY, 2022)
Adenoids and tonsils have gained interest as a new in vivo model to study local immune functions and virus reservoirs. Especially herpesviruses are interesting because their prevalence and persistence in local lymphoid tissue are incompletely known. Our aim was to study herpesvirus and common respiratory virus infections in nonacutely ill adenotonsillar surgery patients. Adenoid and/or palatine tonsil tissue and nasopharyngeal aspirate (NPA) samples were collected from elective adenoidectomy (n = 45) and adenotonsillectomy (n = 44) patients (median age: 5, range: 1-20). Real-time polymerase chain reaction was used to detect 22 distinct viruses from collected samples. The overall prevalence of herpesviruses was 89% and respiratory viruses 94%. Human herpesviruses 6 (HHV6), 7 (HHV7), and Epstein-Barr virus (EBV) were found, respectively, in adenoids (33%, 26%, 25%), tonsils (45%, 52%, 23%), and NPA (46%, 38%, 25%). Copy numbers of the HHV6 and HHV7 genome were significantly higher in tonsils than in adenoids. Patients with intra-adenoid HHV6 were younger than those without. Detection rates of EBV and HHV7 showed agreement between corresponding sample types. This study shows that adenoid and tonsil tissues commonly harbor human herpes- and respiratory viruses, and it shows the differences in virus findings between sample types.